Acetic Acid Bacteria and the Production and Quality of Wine Vinegar - Albert Mas; María Jesús Torija; María del Carmen García-Parrilla; Ana María Troncoso (The Scientific World Journal)
The production of vinegar depends on an oxidation process that is mainly performed by acetic acid bacteria. Despite the different methods of vinegar production (more or less designated as either “fast” or “traditional”), the use of pure starter cultures remains far from being a reality. Uncontrolled mixed cultures are normally used, but this review proposes the use of controlled mixed cultures. The acetic acid bacteria species determine the quality of vinegar, although the final quality is a combined result of technological process, wood contact, and aging. This discussion centers on wine vinegar and evaluates the effects of these different processes on its chemical and sensory properties.